Effect of Polyethylene-glycolated Carboxyhemoglobin on Renal Microcirculation in a Rat Model of Hemorrhagic Shock. (November 2019) - Guerci, Philippe; Ergin, Bulent; Kapucu, Aysegul; Hilty, Matthias P.; Jubin, Ronald; Bakker, Jan; Ince, Can
Abstract : Background: Primary resuscitation fluid to treat hemorrhagic shock remains controversial. Use of hydroxyethyl starches raised concerns of acute kidney injury. Polyethylene-glycolated carboxyhemoglobin, which has carbon monoxide–releasing molecules and oxygen-carrying properties, was hypothesized to sustain cortical renal microcirculatory PO2 after hemorrhagic shock and reduce kidney injury. Methods: Anesthetized and ventilated rats (n = 42) were subjected to pressure-controlled hemorrhagic shock for 1 h. Renal cortical PO2 was measured in exposed kidneys using a phosphorescence quenching method. Rats were randomly assigned to six groups: polyethylene-glycolated carboxyhemoglobin 320 mg · kg −1, 6% hydroxyethyl starch (130/0.4) in Ringer's acetate, blood retransfusion, diluted blood retransfusion (~4 g · dl −1 ), nonresuscitated animals, and time control. Nitric oxide and heme oxygenase 1 levels were determined in plasma. Kidney immunohistochemistry (histologic scores of neutrophil gelatinase-associated lipocalin and tumor necrosis factor-α) and tubular histologic damages analyses were performed. Results: Blood and diluted blood restored renal PO2 to 51 ± 5 mmHg (mean difference, −18; 95% CI, −26 to −11; P < 0.0001) and 47 ± 5 mmHg (mean difference, −23; 95% CI, −31 to −15; P < 0.0001), respectively, compared with 29 ± 8 mmHg for hydroxyethyl starch. No differences between polyethylene-glycolated carboxyhemoglobin and hydroxyethyl starch were observed (33 ± 7 mmHg vs. 29 ± 8 mmHg; mean difference, −5; 95% CI, −12 to 3; P = 0.387), but significantly less volume was administered (4.5 [3.3–6.2] vs . 8.5[7.7–11.4] ml; mean rank difference, 11.98; P = 0.387). Blood and diluted blood increased the plasma bioavailability of nitric oxide compared with hydroxyethyl starch (mean rank difference, −20.97; P = 0.004; and −17.13; P = 0.029, respectively). No changes in heme oxygenase 1 levels were observed. Polyethylene-glycolated carboxyhemoglobin limited tubular histologic damages compared with hydroxyethyl starch (mean rank difference, 60.12; P = 0.0012) with reduced neutrophil gelatinase-associated lipocalin (mean rank difference, 84.43; P < 0.0001) and tumor necrosis factor-α (mean rank difference, 49.67; P = 0.026) histologic scores. Conclusions: Polyethylene-glycolated carboxyhemoglobin resuscitation did not improve renal PO2 but limited tubular histologic damages and neutrophil gelatinase-associated lipocalin upregulation after hemorrhage compared with hydroxyethyl starch, whereas a lower volume was required to sustain macrocirculation. Abstract : In a rat model of hemorrhagic shock, comparing fluid resuscitation with blood, diluted blood, hydroxyethyl starch, or polyethylene-glycolated carboxyhemoglobin, all fluids restored urine output and creatinine clearance, but only blood and diluted blood improved renal PO2 . Postresuscitation histologic renal tubular damage was increased compared with nonresuscitated rats but slightly less with blood, diluted blood, and polyethylene-glycolated carboxyhemoglobin compared with hydroxyethyl starch. Restoration of circulatory hemodynamics and kidney microcirculatory PO2 was comparable with polyethylene-glycolated carboxyhemoglobin and balanced hydroxyethyl starch solution.Supplemental Digital Content is available in the text.